2018
DOI: 10.1098/rsif.2018.0335
|View full text |Cite
|
Sign up to set email alerts
|

Drawing power of virtual crowds

Abstract: In 1969, social psychologist Milgram and his colleagues conducted an experiment on a busy city street where passers-by witnessed a set of actors spontaneously looking up towards a building. The experiment showed that the crowd's propensity to mimic the actor's gaze increased with the number of actors that looked up. This form of behavioural contagion is found in many social organisms and is central to how information travels through large groups. With the advancement of virtual reality and its continued applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Collectively these data indicate that participants are quite sensitive to the social contagion of yawning within a virtual environment, which is consistent with recent VR research on other forms of contagious/reflexive behavior (i.e., gaze following) 49 . And yet, surprisingly, the participants were immune to the visual social signals of explicit (Experiments 4 and 5) and implied (Experiments 2 and 3) social presence displayed within this setting; but were extraordinarily sensitive to the unseen real presence of an experimenter outside of VR, i.e., in the testing room.…”
Section: Discussionsupporting
confidence: 88%
“…Collectively these data indicate that participants are quite sensitive to the social contagion of yawning within a virtual environment, which is consistent with recent VR research on other forms of contagious/reflexive behavior (i.e., gaze following) 49 . And yet, surprisingly, the participants were immune to the visual social signals of explicit (Experiments 4 and 5) and implied (Experiments 2 and 3) social presence displayed within this setting; but were extraordinarily sensitive to the unseen real presence of an experimenter outside of VR, i.e., in the testing room.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has emphasized that cue numerosity guides behavioral responses in both human infants (Pun et al, 2016) and primates (Pun et al, 2017) in an effortless and spontaneous manner. Recent work has also shown that group-ratio estimates (e.g., the identification of a group majority vs. minority) dynamically guide human adults' attentional responses in a variety of contexts Gallup et al, 2012;Jorjafki et al, 2018;Sun et al, 2017). Thus, our finding of greater magnitudes of gaze following responses to the gaze direction of the group majority vs. the group minority is consistent with such previous research.…”
Section: Cue Numerosity and Social Informationsupporting
confidence: 90%
“…Finally, as a preregistered exploratory analysis, we also looked for non-linear patterns in the data, based on the fact that previous research has mostly found an asymptotic relationship between group size and gaze following (Gallup et al, 2012;Jorjafki et al, 2018;Milgram et al, 1969). Non-linear models were fitted by replacing the linear group size term with a linear b-spline term with a single knot at the average group size (Hastie et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In one of the first studies to make this point, Milgram, Bickman, and Berkowitz (1969) asked a group of confederates to walk down a New York City street before suddenly stopping and looking up at a tall building. They then measured how often unaware passersby imitated the group's behavior and found a clear positive relationship between the size of the stimulus group and the probability of looking up (see also Gallup et al, 2012;Jorjafki et al, 2018;Knowles & Bassett, 1976).…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation